Analysis of Social Studies Educational Videos’ Role in Shaping Fifth-Grade Students’ Environmental Care Character - Virda Widia Putri; Nurdinah Hanifah; Ani Nur Aeni (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This research is motivated by the low consistency of students' environmental care character and the limited use of digital media in social studies learning to support character education. This study aimed to analyze the implementation of educational videos in social studies learning, their role in shaping environmental care character, and the forms of environmental care character developed among fifth-grade students at SD Negeri 2 Cantilan. This study employed a qualitative approach using an explanatory case study with a single case embedded design. The participants consisted of the principal, one fifth-grade teacher, and seven fifth-grade students, totaling nine informants. Data were collected through non-participant observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model. The trustworthiness of data was examined through source and technique triangulation. The results showed that: (1) educational videos were implemented systematically through planning, implementation, and reflection stages; (2) educational videos fostered students’ environmental awareness and caring attitudes through contextual and engaging learning materials; and (3) students’ environmental care character developed in the dimensions of knowledge, attitudes, and behavior, indicated by an increase in observation scores from 23.7 to 35.9, representing an improvement of 33.7%. Students also demonstrated positive environmental behaviors, such as maintaining classroom cleanliness, disposing of waste properly, and conserving water and electricity. Therefore, educational videos proved effective in supporting the development of environmental care character among elementary school students.